Oxidative stress, inflammatory settings, and microRNA regulation in the recurrent implantation failure patients with metabolic syndrome. (11th August 2019) - Sheikhansari, Golshan; Soltani‐Zangbar, Mohammad Sadegh; Pourmoghadam, Zahra; Kamrani, Amin; Azizi, Ramyar; Aghebati‐Maleki, Leili; Danaii, Shahla; Koushaeian, Ladan; Hojat‐Farsangi, Mohammad; Yousefi, Mehdi
Abstract: Problem: Increased oxidative stress (OS) and inflammatory factors in metabolic syndrome (MS) patients are considered as risk factors for recurrent implantation failure (RIF). The aim of this study was to investigate OS markers, inflammatory factors, related microRNAs (miRNA) expression, and cytokine and transcription factors RNA expression. Method of study: We evaluated the frequency of helper T (Th) 17 and regulatory T (Treg) cells in recurrent implantation failure (RIF) women with or without MS. miRNA expression, an inflammatory cytokine, and transcription factors were measured by real‐time PCR. The level of interleukin (IL)‐1β, IL‐6, IL‐17, tumour necrosis factor‐alpha (TNF‐alpha) and chemokine (C‐C motif) ligand 2 (CCL‐2), and C‐X‐C motif chemokine ligand 8 (CXCL‐8) were measured by enzyme‐linked immunosorbent assay (ELISA). OS markers were evaluated by spectrophotometric assay. Th17 and Treg cell frequencies were determined by flow cytometry. Results: The expression of AP1, NF‐κB, FOXP3, miRNA‐21; serum or plasma level of OS markers (ie, nitric oxide, total oxidant status, and myeloperoxidase); serum level of inflammatory factors (ie, IL1‐β, IL‐6, IL‐17, TNF‐alpha, CXCL‐8, and CCL‐2); and frequency of Th17 cells were increased in RIF‐MS patients in comparison with RIF women without MS (RIF‐NMS) and control group. The expression of miRNA‐223 and 146a, antioxidant enzymes, namely superoxide dismutase (SOD) and catalase (CAT), and frequency of Treg also declined in RIF‐MS patients. Conclusion: Overall, our findings suggest that MS in RIF patients causes increased inflammatory factors and OS, which in turn leads to implantation failure.